The Gamification of Meditation: A Randomized-Controlled Study of a Prescribed Mobile Mindfulness Meditation Application in Reducing College Students' Depression. (August 2019) - Fish, Matthew T.; Saul, Amelia D.
Objective. Roughly35% of college students report depression as a significant concern, which unaddressed, can lead to an increased likelihood to quit school and develop comorbid conditions. Traditional depression interventions are useful; however, they are often expensive, stigmatizing, tedious, and time-intensive. We examined a prescribedmindfulness meditation regimen, which incorporatesgamification principles, in reducingsymptoms of depression compared to a control group. Materials and methods. We recruited and randomly assigned 72 college students to an experimental group (n = 33) or a control group (n = 39). The prescription for experimfiental group participants was ten 10-minutemobile mindfulness meditation sessions over a 14-day period; control group participants continued with business as usual. ThePatient Health Questionnaire (PHQ-9) was used to test our hypothesis. Results. Repeated-measures ANOVA demonstrated a significant interaction of group by time fordepression scores, supporting the hypothesis that experimental group participants would significantly decrease their depression symptom severity compared to control group participants post-intervention. Within-subjects contrasts and between-group analyses showed a significant decreasein depression symptom severity scores. Conclusion. Prescribed use of a gamified mindfulness meditation application significantly decreased depression symptom severity as measured by the PHQ-9. College students and mental health providers should consider thesefun, inexpensive, and non-stigmatizing applications as a feasible interventionfor college students to improve symptoms associated with depression .